2018
DOI: 10.1002/jcla.22596
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of variant RHD genotypes among donors and patients of mixed origin with serologic weak‐D phenotype

Abstract: The frequency of partial D among mixed individuals with serologic weak-D phenotype is high. They should be managed as D-negative patients until molecular tests are complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…[8][9][10] It has been recently suggested that weak D types 1, 2, and 3 represent less than 30 percent of the serologic weak D phenotypes identified among Brazilians, who are intensely racially mixed. 11 Relatively high frequencies of weak D type 38 and weak D type 11 in this population were also shown, 11,12 which is an interesting finding, since these variants are infrequent among white individuals and not reported among people of African ancestry.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…[8][9][10] It has been recently suggested that weak D types 1, 2, and 3 represent less than 30 percent of the serologic weak D phenotypes identified among Brazilians, who are intensely racially mixed. 11 Relatively high frequencies of weak D type 38 and weak D type 11 in this population were also shown, 11,12 which is an interesting finding, since these variants are infrequent among white individuals and not reported among people of African ancestry.…”
supporting
confidence: 60%
“…The higher-than-expected prevalence of weak D type 38 among Brazilians has been previously suggested by some studies, which focused their analyses on samples with low expression of D. 11,12,20,21 The frequency of this D variant significantly differed from that previously calculated for individuals of European descent. 22 In fact, in some large cohorts of European individuals screened for weak D phenotype, this variant was not encountered.…”
Section: Discussionmentioning
confidence: 70%
“…Genetic alterations and mutations cause quantitative or qualitative changes in the D antigen expression, resulting in a variety of D alleles. These RHD alleles are classified as weak D, partial D, and Del 11 . Mutations in the weak D variants lead to decreased RHD gene expression without altering the protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…We have observed that when the molecular report does not provide an interpretation and recommendation, clinical practictioners not experienced in blood group genetics hesitate to interpret RHD genotyping results as D+ or D−. For the purposes of RhIG adminstration and transfusion, interpretation of an RHD genotype requires not only pertinent experience but also knowledge of the history 2,5 as well as the current evolving data [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and literature reports 15,16,[23][24][25][26] of the risks for alloimmunization associated with specific RHD genotypes. 27 Hospital computer systems may require updating to accomodate new requirements, such as the ability to change a prior serologic D typing result, when it is overridden by a different D type based on RHD genotyping results.…”
mentioning
confidence: 99%